2011
DOI: 10.1136/bcr.11.2010.3502
|View full text |Cite
|
Sign up to set email alerts
|

Superior vena cava syndrome caused by embolisation of liquid Onyx

Abstract: Superior vena cava syndrome (SVCS) is usually caused by a malignancy or the presence of an intravascular device in a central vein. A 74-year-old male with a history of a superior vena cava (SVC) stent underwent embolisation of a brain arterio-venous malformation through the right meningeal artery with liquid Onyx. Two weeks later he presented with acute respiratory failure, upper airway obstruction, plethora, varices of the chest wall and stridor. He was intubated and placed on mechanical ventilatory support. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The only other case of migrated Onyx in the literature [10] described migration of Onyx into a superior vena cava (SVC) stent following embolisation of a dural arteriovenous malformation through the right meningeal artery. The patient developed SVC syndrome and was treated by ''angioplasty of the stent and removal of the Onyx from a common femoral vein approach by interventional radiology''.…”
Section: Discussionmentioning
confidence: 97%
“…The only other case of migrated Onyx in the literature [10] described migration of Onyx into a superior vena cava (SVC) stent following embolisation of a dural arteriovenous malformation through the right meningeal artery. The patient developed SVC syndrome and was treated by ''angioplasty of the stent and removal of the Onyx from a common femoral vein approach by interventional radiology''.…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al [7] reported unintended Onyx migration into the middle inner ear 6 years following embolization of a right temporal AVM. Crusio et al [8] documented Onyx migration into a right atrium stent 2 weeks after embolization of the right meningeal artery for a dural AVM. Several cases of delayed Onyx migration have also been reported in patients with dural arteriovenous fistulas (DAVFs).…”
Section: Discussionmentioning
confidence: 99%